Climate Change and Cities : First Assessment Report of the Urban Climate Change Research Network / [electronic resource] - Rosenzweig, Cynthia; Solecki, William D.; Hammer, Stephen A.; Mehrotra, Shagun (Cambridge : Cambridge University Press, 2011)
Urban areas are home to over half the world's people and are at the forefront of the climate change issue. The need for a global research effort to establish the current understanding of climate change adaptation and mitigation at the city level is urgent. To meet this goal a coalition of international researchers - the Urban Climate Change Research Network (UCCRN) - was formed at the time of the C40 Large Cities Climate Summit in New York in 2007. This book is the First UCCRN Assessment Report on Climate Change and Cities. The authors are all international experts from a diverse range of cities with varying socio-economic conditions, from both the developing and developed world. It is invaluable for mayors, city officials and policymakers; urban sustainability officers and urban planners; and researchers, professors and advanced students.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Urban ecology (Sociology); Climate change mitigation; Urban policy